The Effect Of People, Physical Evidence, Process, and Price Fairness On Patient Satisfaction At ABC Clinic, South Jakarta - Mumtaza, Dara Daula; Bernarto, Innocentius (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This study examined how factors such as people, tangible evidence, procedures, and price fairness affected patient satisfaction at ABC clinic, South Jakarta. The population in this study were patients who had visited and carried out swab procedures at the ABC Swab Clinic in December 2022-May 2023. Sampling in this study used purposive sampling, while the sampling technique used non-probability sampling technique. This study involved 389 clinical patients who were willing to be respondents. Data collection was carried out by distributing questionnaires containing 28 questions using a Likert Scale of 1 – 5. The data were analyzed using the Partial Least Square (PLS)-based Structural Equation Modeling (SEM) method and two models were evaluated, namely the outer model was used to find out whether there was a correlation between the indicators and their latent variables and the inner model to see how the quality of a research model was. to perform a significance test in the correlation between variables. The results of this study state that people, physical evidence, process and price fairness have a positive and significant effect on patient satisfaction at the South Jakarta ABC Swab Clinic.